Chemical vapour deposition and characterization of uniform bilayer and trilayer MoS2 crystals. Issue 47 (14th November 2016) - Zobel, Adam; Boson, Alex; Wilson, Peter M.; Muratov, Dmitry S.; Kuznetsov, Denis V.; Sinitskii, Alexander
Abstract : We report a chemical vapor deposition procedure for MoS2 growth from MoO3 and S, which yields predominantly bilayer and trilayer MoS2 triangular islands. Abstract : Molybdenum disulfide (MoS2 ) is a promising two-dimensional semiconductor for applications in electronics, optoelectronics and catalysis. Chemical vapor deposition (CVD) is a popular approach for the large-scale growth of thin MoS2 crystals. As the properties of MoS2 strongly depend on the number of layers, it is important to reliably grow MoS2 crystals with different thicknesses. In this paper, we present a CVD procedure for MoS2 growth from MoO3 and S, which yields predominantly bilayer and trilayer MoS2 triangular islands as opposed to monolayer MoS2 triangles typically observed in similar CVD experiments. The growth of bilayer and trilayer MoS2 crystals is achieved by increasing the flow rate of sulfur after the original nucleation of MoS2 triangles. Most bilayer MoS2 crystals are uniform in height, such that in a typical crystal the top layer fully extends to the edges of the bottom layer. While trilayer MoS2 crystals grown by this procedure are in general less uniform than bilayers and often form terraced structures, it is still common to observe uniform trilayer MoS2 triangles as well. In addition to standard characterization methods for MoS2, such as Raman spectroscopy, atomic force microscopy and photoluminescence microscopy we demonstrate that scanning electron microscopy can be used to distinguish between monolayer and few-layered MoS2 flakes at low accelerating voltages. The field-effect transistors based on CVD-grown MoS2 triangles have electron mobilities reaching ∼10 cm 2 V −1 s −1 and ON/OFF ratios reaching ∼10 5 . The reported CVD procedure can be used for growing large quantities of uniform bilayer and trilayer MoS2 crystals for materials studies.